If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4y = -25 Solving 5x + -4y = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 5x + -4y + 4y = -25 + 4y Combine like terms: -4y + 4y = 0 5x + 0 = -25 + 4y 5x = -25 + 4y Divide each side by '5'. x = -5 + 0.8y Simplifying x = -5 + 0.8y
| x+x-4+x-4*2=68 | | 16x^2-64x-4=0 | | 2.3(x)^(1/2) | | sin^2(2x)+3sin(2x)-2=0 | | 10x^2+20x-45=8 | | 6x^2-20x-154=0 | | 7-4(x+6)= | | 4t-1=-3(3t-4) | | 12=-2y | | X/-x-90=0 | | 3(2x)-9x-4=2x+12 | | 4x+x^2=-2.5 | | y=4.5(x-27) | | sin^2(pi/6) | | 2(5x-6y)-(2x+3y)=equation | | (b-9)(b+9)= | | 4x^2-15x+36=6x+9 | | 3x+24=2x^2-7x+40 | | 12+5x=7x-12 | | 7x+2=2(7x+2)+8 | | 75-what+10=60 | | 3(-1+2r)+9= | | 3r-2=22 | | -3(3p+2)-2(5-8p)=3(5+2p) | | 2(x-1)(x+5)=2-x(2x+16) | | Y=-6x-y | | (2f-3)f=18 | | 9d+4=94 | | 4t-11=29 | | p-3/7=6 | | x^2-16+(x+4)(x+1)=0 | | 2v-3=0 |